THE ANALYSIS OF THE SPECIFICITY OF INNOVATIVE ACTIVITY IN THE CONSTRUCTION INDUSTRY - Alexey A. Solovey (Статистика и экономика)
The paper attempts to identify the specifics of innovation in construction.